2005
DOI: 10.1007/s00530-005-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimum adaptation trajectories for streamed multimedia

Abstract: Most adaptive delivery mechanisms for streaming multimedia content do not explicitly consider user-perceived quality when making adaptations. We propose that an optimal adaptation trajectory through the set of possible encodings exists and that it indicates how to adapt encoding quality in response to changes in network conditions to maximize user-perceived quality. Such an optimum adaptation trajectory can be used with any transmission adaptation policy. We describe the subjective tests we carried out to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In the future, it would be desirable to develop an adaptive decision strategy of scalability options for resource-constrained networks by taking into account the drawn observations in this paper as guidelines. Previously, there have been some work of proposing such strategies (e.g., [8], [23]), which are not usually based on thorough subjective evaluation across all three scalability dimensions. Moreover, it is useful to develop objective quality measures of video sequences generated by scalable video coding based on the results reported here, which can be used in adaptive strategies for real-time automatic quality measurement and monitoring of delivered content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, it would be desirable to develop an adaptive decision strategy of scalability options for resource-constrained networks by taking into account the drawn observations in this paper as guidelines. Previously, there have been some work of proposing such strategies (e.g., [8], [23]), which are not usually based on thorough subjective evaluation across all three scalability dimensions. Moreover, it is useful to develop objective quality measures of video sequences generated by scalable video coding based on the results reported here, which can be used in adaptive strategies for real-time automatic quality measurement and monitoring of delivered content.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [7] tried to find the optimal temporal resolution over a range of bandwidths through subjective quality evaluation for motion-compensated wavelet/ subband video coding. In [8], it was shown that there exists an optimal adaptation trajectory in the space of possible combinations of spatial and temporal resolutions for MPEG-4 video sequences. The work presented in [9] provides subjective quality test results of low bit rate video sequences encoded by H.263 and H.264/AVC by considering different dimensions such as spatial resolution, temporal resolution, and bit rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [14] investigated the optimal temporal resolution over a range of bandwidths through subjective quality evaluation for the motion-compensated wavelet/subband video coding (MCSBC). The work presented in [4] showed that, through subjective tests with MPEG-4 video sequences, there exists an optimal adaptation trajectory in the space of possible encodings (i.e. combinations of spatial and temporal resolutions), which maximizes visual quality.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these adaptive solutions gradually vary the video streams' characteristics in response to fluctuating network conditions thereby allowing for the perceived quality to be gracefully adapted. Among the proposed solutions are layer-based schemes such as [14,16], object-based adaptation mechanisms [17], fine-granular scalability-based solutions [18] and perception-based approaches [19]. Admission and error control that are used along with the adaptive solutions in either centralized [15] or distributed approaches [20], are employed in order to increase their effectiveness.…”
Section: Introductionmentioning
confidence: 99%